Are load-velocity profile parameters important for 200 m front crawl performance? - Olstad, B. H.; Ophus, E.; Buvarp, M. H.; Ljødal, I.; Gonjo, T. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
Load-velocity profiles have shown the importance of swimming-specific strength and velocity capabilities for male front crawl sprint performance (Gonjo et al., 2021). Whether these relationships also exist for middle-distance swimming is unknown. The purpose of the present study was therefore to investigate whether load-velocity profile outcome parameters would be related to 200 m front crawl performance for national elite junior swimmers.